Strain behavior of thin film PbZr0.3Ti0.7O3 (30/70) examined through piezoforce microscopy - Dunn, Steve (American Institute of Physics (AIP), 2003)
Using an atomic force microscope (AFM) modified to perform PiezoAFM we have investigated the piezoelectric response of sol-gel thin film lead zirconate titanate (PZT 30/70, PbZr0.3Ti0.7O3) on Pt-Ti/SiO2/Si to a quasi DC electric field. The films were produced by spin coating a PZT 30/70 sol onto a selected substrate and firing at 520ºC. This generated a film that was highly [111] orientated and single phase perovskite. By applying a sinusoidal 2Hz AC waveform between the AFM cantilever and ground we have generated strain-field, or butterfly loops for the PZT film. PiezoAFM butterfly loops show that the localised piezoelectric response for PZT varies depending on the sign of the applied field. The degree of asymmetry in the hysteresis loop has been attributed to charge trapping at the electrode-PZT interface generating a system that can preferentially re-pole in one direction. The charge trapped at the interface has an overwhelming effect on the polarisability of the film. Coercive fields have been calculated from the minimum point of the strain before reversal for the system and are shown to be -30V/μm and +32V/μm in absolute terms and -23V/μm and +39V/μm in terms relative to the charge trapped at the electrode interface. δ33 values obtained for the PZT thin film 2 investigated ranged from 30 to 40pm/V. The maximum strain of the system was shown at applied biases of +/-10V and was 0.3% at a bias of +10V, although at this field the sample was not showing saturated behaviour. By relating the offset of the butterfly loops to the charge density generated by defects at the PZT-electrode interface, calculated to be 0.025Cm-2, an estimate of the number of defects at the interface has been drawn. The concentration of defects at the interface is 1 defect for every 6nm2 of surface, representing 1 defect for every 40 unit cells or 2.5% of unit cells being defected.